A porous anorthite aggregate, a preparation method and application thereof
Patent Information
- Application Number
- CN202611155479.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-16
AI Technical Summary
[0012]有鉴于此,本发明的目的在于提出一种多孔钙长石骨料及其制备方法和应用,以解决传统钙长石骨料原料成本高、脱硫灰资源化利用工艺稳定性差、成品性能波动大的问题,该多孔钙长石骨料具有低成本、绿色低碳、烧结稳定性强的效果,适配玻璃窑炉、工业高温窑炉隔热工况,实现大宗脱硫灰固废高值化利用
[0036] The present invention also provides the application of the porous calcium feldspar aggregate in kilns, heat-insulating furnace linings, and refractory materials.
Smart Images

Figure CN122916692A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of refractory materials technology, and in particular to a porous calcium feldspar aggregate, its preparation method, and its application. Background Technology
[0002] Anorthite (CaO·Al2O3·2SiO2) possesses low thermal conductivity, good thermal insulation and high-temperature stability, as well as excellent resistance to reducing atmospheres and alkaline media erosion, thermal shock resistance, and spalling resistance. It is widely used in high-temperature fields such as metallurgy, building materials, and glass furnaces. Traditional anorthite aggregates often use high-purity chemical raw materials (calcium carbonate, alumina, silicon dioxide, etc.), which results in high raw material costs, high energy consumption, and high carbon emissions.
[0003] Desulfurization ash is a large amount of industrial solid waste generated during the desulfurization of flue gas from power plants and steel sintering plants. Its main components are CaO and SO3, and it is rich in calcium, which can be used as an inexpensive calcium source for the preparation of anorthite. At present, desulfurization ash is mostly disposed of by stockpiling and simple landfill, which has a low utilization rate and easily causes sulfur pollution and land occupation.
[0004] The existing technology has the following drawbacks:
[0005] (1) Traditional calcium source synthesis method: high cost and low solid waste utilization rate
[0006] Traditional anorthite materials are mostly synthesized using a single calcium source such as calcium carbonate, calcite, or chemically pure CaO through high-temperature solid-state reactions. This method offers high-purity raw materials and mature technology, but it suffers from problems such as high calcium source costs, high resource dependence, and high carbon emissions.
[0007] (2) In-situ sintering of desulfurization ash: low temperature expansion, high temperature overheating, and extremely narrow sintering window.
[0008] When using desulfurized ash as a calcium source for direct sintering to prepare anorthite materials, the rapid decomposition of CaSO4 at low temperatures generates large amounts of SO2, CO2, and other gases, leading to significant expansion, loose structure, and susceptibility to cracking of the green body. At high temperatures, excessive liquid phase is easily generated, resulting in abnormal grain growth, rapid shrinkage of the green body, softening and bulging, deformation, and collapse. The stable sintering temperature range is extremely narrow, and even slight temperature fluctuations result in defective products, making continuous and stable industrial production difficult.
[0009] (3) Conventional process control method: poor reaction matching, large performance fluctuations, and insufficient overall performance.
[0010] Traditional preparation processes fail to coordinate and control the thermal decomposition of desulfurization ash and the in-situ formation of anorthite, resulting in incomplete intermediate phase transformation and low purity of the anorthite main crystalline phase. Simultaneously, the mismatch between gas escape and the densification rate of the green body leads to uneven pore distribution, numerous defects, and significant fluctuations in material strength and thermal insulation performance, making it difficult to meet the requirements for high-temperature kiln linings.
[0011] Each of the aforementioned individual methods has certain limitations, making it difficult to achieve an ideal balance between cost, industrialization, and material performance. Therefore, developing a porous calcium feldspar aggregate with desulfurization ash as a calcium source, a wide sintering window, and stable performance, as well as its preparation method, has significant economic and environmental value. Summary of the Invention
[0012] In view of this, the purpose of this invention is to propose a porous calcium feldspar aggregate, its preparation method and application, to solve the problems of high raw material cost, poor process stability of desulfurization ash resource utilization, and large fluctuations in finished product performance of traditional calcium feldspar aggregate. This porous calcium feldspar aggregate has the effects of low cost, green and low carbon, and strong sintering stability. It is suitable for the heat insulation conditions of glass kilns and industrial high-temperature kilns, and realizes the high-value utilization of large quantities of desulfurization ash solid waste.
[0013] To achieve the above objectives, this invention provides a porous calcium feldspar aggregate comprising the following raw materials by weight percentage: 24-30% calcium source, 40-50% aluminum source, 26-30% aluminum-silicon source, and a binder, wherein the binder accounts for 2-5% of the total amount of the calcium source, aluminum source, and aluminum-silicon source; the calcium source is desulfurized ash, with a CaO content ≥57wt% and an SO3 content ≥25wt%; the porous calcium feldspar aggregate is obtained by molding and drying the raw materials, followed by gradient-stage heating to 1100-1350℃ and holding for calcination. Staged sintering can match the sulfate decomposition rate of the desulfurized ash with the densification rate of the green body, suppressing low-temperature expansion cracking and high-temperature overheating deformation.
[0014] Preferably, the desulfurization ash is power plant desulfurization ash or sintering desulfurization ash, wherein the power plant desulfurization ash has a CaO content ≥65wt% and an SO3 content ≥25wt%; and the sintering desulfurization ash has a CaO content ≥57wt% and an SO3 content ≥36wt%.
[0015] Preferably, the aluminum source includes aluminum recycled clinker powder, wherein the aluminum recycled clinker powder contains Al2O3 ≥ 51wt%, SiO2 ≥ 36wt%, and harmful impurities ≤ 1wt%.
[0016] Preferably, the aluminum-silicon source includes coal gangue powder, wherein the coal gangue powder contains SiO2 ≥ 65wt% and Al2O3 ≥ 23wt%.
[0017] The particle size of the desulfurization ash, aluminous recycled clinker powder, and coal gangue powder is controlled to be ≤200 mesh (74μm) to ensure that the components are mixed evenly and provide sufficient reactivity to promote the solid-phase synthesis of anorthite.
[0018] The porous calcium feldspar aggregate of this invention uses calcium feldspar (CaO·Al2O3·2SiO2) as the main crystalline phase, and uses in-situ pore-forming by desulfurization ash thermal decomposition gas, with an apparent porosity of ≥28% and a bulk density of 1.60~2.10 g / cm³.
[0019] The aggregate linear shrinkage rate is -2.05%~5.66%, and the volume shrinkage rate is -4.69%~17.64%. It has stable dimensions and a wide sintering window, making it suitable for high-temperature heat-insulating furnace linings.
[0020] Preferably, the binder is one of deionized water, distilled water, or ultrapure water. The deionized water is added in solution form during the raw material mixing process to achieve uniform dispersion in the dry powder, ensuring consistent molding strength of the green body and avoiding localized over-wetting or dryness.
[0021] The core of this invention lies in the synergistic effect of three mechanisms:
[0022] (1) Solid waste co-production mechanism: Sufficient CaO is provided by desulfurization ash as calcium source, Al2O3 is provided by aluminum recycled clinker powder as aluminum source, and SiO2 is provided by coal gangue powder as silicon source. The three components are matched according to the stoichiometric ratio of calcium feldspar, and calcium feldspar is generated in situ as the main crystalline phase at high temperature, replacing the traditional high-purity calcium source, significantly reducing the cost of raw materials, and realizing the high-value utilization of bulk solid waste.
[0023] (2) Sintering stability control mechanism: adopting a multi-stage segmented heating and constant temperature short heat preservation system to control the decomposition rate of sulfate in desulfurization ash to match the densification rate of the green body, solve the problems of low temperature expansion cracking and high temperature overheating deformation, broaden the sintering temperature window, and improve the dimensional stability of the product.
[0024] (3) Porous structure self-generation mechanism: SO2 and CO2 gases generated by the thermal decomposition of desulfurization ash are used to create pores in situ without the need for additional pore-forming agents. A pore structure is formed inside the green body, which takes into account both high porosity and certain strength, ensuring the excellent thermal insulation performance of the material.
[0025] The three mechanisms work synergistically: the solid waste ratio ensures that the calcium feldspar phase is the main phase, the sintering process ensures stable molding, and the gas self-generated pores ensure porous insulation. The coupling of these three mechanisms enables low-cost, high-performance, and green preparation.
[0026] The present invention also provides a method for preparing the porous calcium feldspar aggregate, comprising the following steps:
[0027] Step 1: Dry mix the calcium source, aluminum source, and aluminum-silicon source according to the formula until uniform;
[0028] Step 2: Add the specified amount of binder to the mixed powder obtained in Step 1 and mix well;
[0029] Step 3: Press the mixture obtained in Step 2 into a blank;
[0030] Step 4: Let the blank from Step 3 stand still, dry, and shape it;
[0031] Step 5: Using gradient segmented temperature-controlled sintering, the dried and shaped green body is kept at 1100~1350℃ for 2~4 hours, and after cooling, porous calcium feldspar aggregate is obtained.
[0032] In step three, the pressing pressure is 100~150MPa, and the holding time is 10~20s.
[0033] The process parameters for gradient segmented temperature-controlled sintering in step five are as follows: heating from 50-200℃ at a rate of 2-6℃ / min; then heating to 1000℃ at a rate of 5-10℃ / min; and finally heating to 1100-1350℃ at a rate of 2-5℃ / min and holding for 2-4 hours. The firing regime adopts a strategy of "segmented temperature control at medium and low temperatures, and sufficient holding at high temperatures." Low-temperature segmentation is used to match the kinetics of desulfurization ash decomposition and gas generation with the densification of the green body, preventing cracking; high-temperature holding ensures complete decomposition of sulfates, full conversion of the mesophase into anorthite, and the acquisition of a stable porous structure.
[0034] Preferably, the process parameters for the gradient segmented temperature-controlled sintering are: 50-200℃ at a rate of 2-6℃ / min; then at a rate of 5-10℃ / min to 1000℃; then at a rate of 2-6℃ / min to 1100℃ and hold for 2-3 hours; and finally at a rate of 2-4℃ / min to 1200-1350℃ and hold for 1-2 hours.
[0035] More preferably, the process parameters for the gradient segmented temperature-controlled sintering are as follows: 50-200℃ at a rate of 5℃ / min; then at a rate of 10℃ / min to 700℃; then at a rate of 5℃ / min to 1000℃; then at a rate of 3℃ / min to 1100℃ and hold for 2-3 hours; and finally at a rate of 2℃ / min to 1200℃ and hold for 1-2 hours.
[0036] The present invention also provides the application of the porous calcium feldspar aggregate in kilns, heat-insulating furnace linings, and refractory materials.
[0037] The beneficial effects of this invention are as follows: This invention employs a low-temperature slow-firing, medium-temperature stable-firing, and high-temperature short-insulation process to solve the problems of low-temperature expansion and high-temperature over-firing of desulfurization ash, ensuring controllable sulfur emissions and producing porous calcium feldspar aggregate with high porosity, dimensional stability, and excellent thermal insulation. This invention achieves high-value utilization of bulk desulfurization ash, with low raw material costs, a green process, and a wide sintering window, making it suitable for the field of thermal insulation and refractory materials for high-temperature industrial kilns, thus offering both economic and environmental benefits. Attached Figure Description
[0038] To more clearly illustrate the technical solutions in this invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only for this invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0039] Figure 1 XRD patterns of samples prepared for the optimal proportion of desulfurization ash in segmented sintering power plants / metallurgical sintering.
[0040] Figure 2 SEM images of the cross-section of a sample prepared for the optimal proportion of desulfurization ash in segmented sintering power plants / metallurgical sintering. Detailed Implementation
[0041] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.
[0042] It should be noted that, unless otherwise defined, the technical or scientific terms used in this invention should have the ordinary meaning understood by one of ordinary skill in the art to which this invention pertains. Terms such as "comprising" or "including" mean that the element or object preceding the word encompasses the elements or objects listed following the word and their equivalents, without excluding other elements or objects.
[0043] Examples 1-7 of the present invention prepared porous calcium feldspar aggregate samples by sintering according to the proportions in Table 1 (all raw material amounts are weight percentages). The preparation method of the porous calcium feldspar aggregates all adopts the following steps:
[0044] Step 1: Dry powder mixing. Weigh each raw material according to the ratio. First, add the desulfurization ash, aluminum recycled clinker powder, and coal gangue powder to the high-speed mixer and dry mix for 30-60 minutes until uniform.
[0045] Step 2: Adding binder. Add 2-5% of deionized water (by weight of the total raw materials) to the mixed powder and continue stirring for 5-10 minutes until the mixture is homogeneous, thus obtaining the mixed powder.
[0046] Step 3: Dry pressing is performed using machine pressing. The mixture from Step 2 is loaded into the mold and pressed into a blank under a pressure of 100~150MPa for 10~20s.
[0047] Step 4: Molding and Drying. After pressing and molding in Step 3, the sample is left to stand at room temperature for 12 hours, and then transferred to an 80℃ oven to dry for 10 hours.
[0048] Step 5: Segmented sintering. Segmented temperature-controlled sintering is adopted. The dried green body is held at 1100~1350℃ for 2~4 hours. The optimal firing temperature is 1200℃. It is then cooled to room temperature with the furnace to obtain porous calcium feldspar aggregate.
[0049] Table 1. Formulation ratios (wt%) of the examples
[0050]
[0051] Example 1
[0052] A method for preparing anorthosite material: using power plant desulfurization ash, aluminum recycled clinker powder, and coal gangue powder as raw materials, and adding 5wt% deionized water, the above raw materials and deionized water are mixed and ground evenly according to the proportions in Table 1, pressed into a blank, and calcined at 50-200℃ with a heating rate of 5℃ / min; 200-1000℃ with a heating rate of 10℃ / min; and 1000-1200℃ with a heating rate of 5℃ / min, and held at 1200℃ for 3 hours to obtain anorthosite material.
[0053] Example 2
[0054] A method for preparing anorthosite material: using power plant desulfurization ash, aluminum recycled clinker powder, and coal gangue powder as raw materials, and adding 5wt% deionized water, the above raw materials and deionized water are mixed and ground evenly according to the proportions in Table 1, pressed into a blank, and calcined at 50-200℃ with a heating rate of 5℃ / min; 200-1000℃ with a heating rate of 10℃ / min; and 1000-1200℃ with a heating rate of 5℃ / min, and held at 1200℃ for 2 hours to obtain anorthosite material.
[0055] Example 3
[0056] A method for preparing anorthosite material: using power plant desulfurization ash, aluminum recycled clinker powder, and coal gangue powder as raw materials, and adding 5wt% deionized water, the above raw materials and deionized water are mixed and ground evenly according to the proportions in Table 1, pressed into a blank, and calcined at 50-200℃, 5℃ / min; 200-700℃, 10℃ / min; 700-1000℃, 5℃ / min; 1000-1100℃, 3℃ / min; held at 1100℃ for 2h; and calcined at 1100℃, 2℃ / min, and held at 1200℃ for 1h to obtain anorthosite material.
[0057] Example 4
[0058] A method for preparing anorthosite material: using power plant desulfurization ash, aluminum recycled clinker powder, and coal gangue powder as raw materials, and adding 5wt% deionized water, the above raw materials and deionized water are mixed and ground evenly according to the proportions in Table 1, pressed into a blank, and calcined at 50-200℃ with a heating rate of 5℃ / min; and at 200-1200℃ with a heating rate of 4℃ / min, and held at 1200℃ for 3 hours to obtain anorthosite material.
[0059] Example 5
[0060] A method for preparing anorthosite material: using power plant desulfurization ash, aluminum recycled clinker powder, and coal gangue powder as raw materials, and adding 5wt% deionized water, the above raw materials and deionized water are mixed and ground evenly according to the proportions in Table 1, pressed into a blank, and calcined at 50-200℃, 5℃ / min; 200-700℃, 10℃ / min; 700-1000℃, 5℃ / min; 1000-1100℃, 3℃ / min; held at 1100℃ for 2h; and calcined at 1100℃, 2℃ / min, and held at 1200℃ for 1h to obtain anorthosite material.
[0061] Example 6
[0062] A method for preparing anorthosite material: using power plant desulfurization ash, aluminum recycled clinker powder, and coal gangue powder as raw materials, and adding 5wt% deionized water, the above raw materials and deionized water are mixed and ground evenly according to the proportions in Table 1, pressed into a blank, and calcined at 50-200℃, 5℃ / min; 200-700℃, 10℃ / min; 700-1000℃, 5℃ / min; 1000-1100℃, 3℃ / min; held at 1100℃ for 2h; and calcined at 1100℃, 2℃ / min, and held at 1200℃ for 1h to obtain anorthosite material.
[0063] Example 7
[0064] A method for preparing anorthosite material: using power plant desulfurization ash, aluminum recycled clinker powder, and coal gangue powder as raw materials, and adding 2wt% deionized water, the above raw materials and deionized water are mixed and ground evenly according to the proportions in Table 1, pressed into a compact, and calcined at 50-200℃ with a heating rate of 5℃ / min; 200-700℃ with a heating rate of 10℃ / min; 700-1000℃ with a heating rate of 5℃ / min; 1000-1100℃ with a heating rate of 3℃ / min; holding at 1100℃ for 2 hours; and calcined at 1100℃ with a heating rate of 2℃ / min and holding at 1200℃ for 1 hour to obtain anorthosite material.
[0065] Performance testing
[0066] The samples from Examples 1-4 were prepared according to the above method, and after being fired under different conditions, their performance was tested. The results are shown in Table 2.
[0067] Table 2 Performance test results of the embodiment
[0068]
[0069] Results Analysis
[0070] As shown in Table 2:
[0071] 1. Lightweight and Porous: Among Examples 1-4, Example 3 exhibits the highest porosity (40.72%) and the lowest bulk density (1.67 g / cm³), indicating that the in-situ pore-forming mechanism of the desulfurization ash is most fully utilized, resulting in uniform pores and a loose structure within the material. Example 1 has the lowest porosity and the highest density, indicating excessive densification. Examples 2 and 4 have moderate porosity and density.
[0072] 2. Sintering compatibility: Example 3 adopts multi-stage fine temperature control sintering, which can make the decomposition gas generation rate of sulfate in desulfurization ash highly matched with the densification rate of the green body. This avoids both rapid expansion and cracking at low temperature and overheating and shrinkage deformation at high temperature. It has the widest sintering window and the best product consistency, making it suitable for continuous industrial production.
[0073] 3. Raw material compatibility: By changing the raw material ratio within the range defined in the claims, the samples can stably prepare porous calcium feldspar aggregate with an apparent porosity ≥28%, and the thermal conductivity meets the requirements for heat insulation in high-temperature industrial kilns, exhibiting strong process tolerance. Specifically, within the range of 24~30wt% desulfurization ash, higher desulfurization ash content results in stronger in-situ pore-forming effect and lower thermal conductivity; within the range of 40~50wt% recycled aluminum clinker powder, higher recycled aluminum clinker content results in higher green body densification and weaker heat insulation performance; within the range of 2~5wt% added deionized water, higher water content results in smaller firing shrinkage and better dimensional stability.
[0074] Taking all performance factors into account, Example 3 in the above embodiments is the optimal implementation scheme.
[0075] Examples 8-17 show the preparation of porous calcium feldspar aggregate samples by sintering according to the proportions in Table 3 (all raw material amounts are weight percentages).
[0076] Table 3. Formulation ratios (wt%) of the examples
[0077]
[0078] Example 8
[0079] A method for preparing anorthosite material: using metallurgical sintering desulfurization ash, alumina recycled clinker powder, and coal gangue powder as raw materials, and adding 5wt% deionized water, the above raw materials and deionized water are mixed and ground evenly according to the proportions in Table 3, pressed into a compact, and calcined at 50-200℃ with a heating rate of 5℃ / min; 200-1000℃ with a heating rate of 10℃ / min; and 1000-1200℃ with a heating rate of 5℃ / min, and held at 1200℃ for 3 hours to obtain anorthosite material.
[0080] Example 9
[0081] A method for preparing anorthosite material: using metallurgical sintering desulfurization ash, alumina recycled clinker powder, and coal gangue powder as raw materials, and adding 5wt% deionized water, then mixing and grinding the above raw materials and deionized water evenly according to the proportions in Table 3, pressing the mixture into a compact, and calcining it under the following conditions: 50-200℃, 5℃ / min heating; 200-1000℃, 10℃ / min heating; 1000-1200℃, 5℃ / min heating, and holding at 1200℃ for 2 hours to obtain anorthosite material.
[0082] Example 10
[0083] A method for preparing anorthosite material: using metallurgical sintering desulfurization ash, alumina recycled clinker powder, and coal gangue powder as raw materials, and adding 5wt% deionized water, the above raw materials and deionized water are mixed and ground evenly according to the proportions in Table 3, pressed into a compact, and calcined at 50-200℃, 5℃ / min; 200-700℃, 10℃ / min; 700-1000℃, 5℃ / min; 1000-1100℃, 3℃ / min; held at 1100℃ for 2h; and calcined at 1100℃, 2℃ / min, and held at 1200℃ for 1h to obtain anorthosite material.
[0084] Example 11
[0085] A method for preparing anorthosite material: using metallurgical sintering desulfurization ash, alumina recycled clinker powder, and coal gangue powder as raw materials, and adding 5wt% deionized water, then mixing and grinding the above raw materials and deionized water evenly according to the proportions in Table 3, pressing the mixture into a compact, and calcining it at 50-200℃ with a heating rate of 5℃ / min; and at 200-1200℃ with a heating rate of 4℃ / min, and holding at 1200℃ for 3 hours to obtain anorthosite material.
[0086] Example 12
[0087] A method for preparing anorthosite material: using metallurgical sintering desulfurization ash, alumina recycled clinker powder, and coal gangue powder as raw materials, and adding 5wt% deionized water, the above raw materials and deionized water are mixed and ground evenly according to the proportions in Table 3, pressed into a compact, and calcined at 50-200℃, 5℃ / min; 200-700℃, 10℃ / min; 700-1000℃, 5℃ / min; 1000-1100℃, 3℃ / min; held at 1100℃ for 2h; and calcined at 1100℃, 2℃ / min, and held at 1200℃ for 1h to obtain anorthosite material.
[0088] Example 13
[0089] A method for preparing anorthosite material: using metallurgical sintering desulfurization ash, alumina recycled clinker powder, and coal gangue powder as raw materials, and adding 5wt% deionized water, the above raw materials and deionized water are mixed and ground evenly according to the proportions in Table 3, pressed into a compact, and calcined at 50-200℃, 5℃ / min; 200-700℃, 10℃ / min; 700-1000℃, 5℃ / min; 1000-1100℃, 3℃ / min; held at 1100℃ for 2h; and calcined at 1100℃, 2℃ / min, and held at 1200℃ for 1h to obtain anorthosite material.
[0090] Example 14
[0091] A method for preparing anorthosite material: using metallurgical sintering desulfurization ash, alumina recycled clinker powder, and coal gangue powder as raw materials, and adding 5wt% deionized water, the above raw materials and deionized water are mixed and ground evenly according to the proportions in Table 3, pressed into a compact, and calcined at 50-200℃, 5℃ / min; 200-700℃, 10℃ / min; 700-1000℃, 5℃ / min; 1000-1100℃, 3℃ / min; held at 1100℃ for 2h; and calcined at 1100℃, 2℃ / min, and held at 1200℃ for 1h to obtain anorthosite material.
[0092] Example 15
[0093] A method for preparing anorthosite material: using metallurgical sintering desulfurization ash, alumina recycled clinker powder, and coal gangue powder as raw materials, and adding 5wt% deionized water, the above raw materials and deionized water are mixed and ground evenly according to the proportions in Table 3, pressed into a compact, and calcined at 50-200℃, 5℃ / min; 200-700℃, 10℃ / min; 700-1000℃, 5℃ / min; 1000-1100℃, 3℃ / min; held at 1100℃ for 2h; and calcined at 1100℃, 2℃ / min, and held at 1200℃ for 1h to obtain anorthosite material.
[0094] Example 16
[0095] A method for preparing anorthosite material: using metallurgical sintering desulfurization ash, alumina recycled clinker powder, and coal gangue powder as raw materials, and adding 5wt% deionized water, the above raw materials and deionized water are mixed and ground evenly according to the proportions in Table 3, pressed into a compact, and calcined at 50-200℃, 5℃ / min; 200-700℃, 10℃ / min; 700-1000℃, 5℃ / min; 1000-1100℃, 3℃ / min; held at 1100℃ for 2h; and calcined at 1100℃, 2℃ / min, and held at 1200℃ for 1h to obtain anorthosite material.
[0096] Example 17
[0097] A method for preparing anorthosite material: using metallurgical sintering desulfurization ash, alumina recycled clinker powder, and coal gangue powder as raw materials, and adding 5wt% deionized water, the above raw materials and deionized water are mixed and ground evenly according to the proportions in Table 3, pressed into a compact, and calcined at 50-200℃, 5℃ / min; 200-700℃, 10℃ / min; 700-1000℃, 5℃ / min; 1000-1100℃, 3℃ / min; held at 1100℃ for 2h; and calcined at 1100℃, 2℃ / min, and held at 1200℃ for 1h to obtain anorthosite material.
[0098] Performance testing
[0099] The samples from Examples 8-17 were prepared according to the above method, and after being fired under different conditions, their performance was tested. The results are shown below.
[0100] Table 4 Performance test results of the embodiments
[0101]
[0102] Results Analysis
[0103] As shown in Table 4:
[0104] Lightweight and porous: Example 10 is a superior example of the sintered desulfurization ash system, with an apparent porosity of 37.85% and a room temperature thermal conductivity of 0.66 W / m·K, showing excellent overall thermal insulation performance; Example 13, sintered desulfurization ash with an upper limit of 30%, has the highest porosity and the lowest thermal conductivity, showing good thermal insulation performance, but the firing shrinkage is too large, making it unsuitable for large-scale mass production; Example 14, aluminum recycled clinker with an upper limit of 50%, is excessively densified, resulting in the weakest thermal insulation performance; the performance of the remaining samples are all within the target range, while the samples with conventional heating have low porosity and poor thermal insulation.
[0105] Sintering compatibility: For multi-stage temperature-controlled samples such as Examples 10 and 12, the sulfate decomposition and compaction rates were well-matched, resulting in significantly lower shrinkage rates compared to samples subjected to conventional temperature increases. These samples exhibited good dimensional stability and a wide sintering window, making them suitable for industrial production. Example 10, with a linear shrinkage rate of 1.18% and a volumetric shrinkage rate of 6.72%, demonstrated the best dimensional stability across the group, indicating the optimal synergistic effect of the process and formulation. All samples underwent the addition of 5wt% deionized water, and no drying cracking occurred.
[0106] Raw material compatibility: Within the range of 24-30 wt% desulfurization ash, 40-50 wt% aluminum clinker, and 26-30 wt% coal gangue, all samples showed an apparent porosity ≥28%, and the thermal conductivity met the insulation requirements of high-temperature kilns, with a wide process tolerance window. Higher concentrations of desulfurization ash resulted in higher porosity and lower thermal conductivity; higher concentrations of aluminum clinker resulted in stronger densification and weaker insulation; and the performance fluctuations within the coal gangue range were relatively small.
[0107] Taking all performance factors into account, Example 10 is the optimal implementation scheme.
[0108] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity. Any omissions, modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the invention should be included within the scope of protection of the invention.
Claims
1. A porous calcium feldspar aggregate, characterized in that, The raw materials include the following weight percentages: 24-30% calcium source, 40-50% aluminum source, 26-30% aluminum-silicon source, and binder, wherein the amount of binder is 2-5% of the total amount of calcium source, aluminum source, and aluminum-silicon source; the calcium source is desulfurized ash, and the desulfurized ash contains ≥57wt% CaO and ≥25wt% SO3; after the raw materials are shaped and dried, porous calcium feldspar aggregate is obtained by gradient segmented heating to 1100-1350℃ and heat preservation calcination.
2. The porous calcium feldspar aggregate according to claim 1, characterized in that, The desulfurization ash is power plant desulfurization ash or sintering desulfurization ash. The power plant desulfurization ash has a CaO content ≥65wt% and an SO3 content ≥25wt%. The sintering desulfurization ash has a CaO content ≥57wt% and an SO3 content ≥36wt%.
3. The porous calcium feldspar aggregate according to claim 1, characterized in that, The aluminum source includes aluminum recycled clinker powder, in which Al2O3 ≥ 51wt%, SiO2 ≥ 36wt%, and harmful impurities ≤ 1wt%.
4. The porous calcium feldspar aggregate according to claim 1, characterized in that, The aluminum-silicon source includes coal gangue powder, in which SiO2 ≥ 65wt% and Al2O3 ≥ 23wt%.
5. The porous calcium feldspar aggregate according to claim 1, characterized in that, The binder includes deionized water, ultrapure water, or distilled water.
6. The method for preparing porous calcium feldspar aggregate according to claim 1, characterized in that, Includes the following steps: Step 1: Dry mix the calcium source, aluminum source, and aluminum-silicon source according to the formula until uniform; Step 2: Add the specified amount of binder to the mixed powder obtained in Step 1 and mix well; Step 3: Press the mixture obtained in Step 2 into a blank; Step 4: Let the blank from Step 3 stand still, dry, and shape it; Step 5: Using gradient segmented temperature-controlled sintering, the dried and shaped green body is kept at 1100~1350℃ for 2~4 hours, and after cooling, porous calcium feldspar aggregate is obtained.
7. The method for preparing porous calcium feldspar aggregate according to claim 6, characterized in that, In step three, the pressing pressure is 100~150MPa, and the holding time is 10~20s.
8. The method for preparing porous calcium feldspar aggregate according to claim 6, characterized in that, The process parameters for gradient segmented temperature-controlled sintering in step five are as follows: increase the temperature from 50-200℃ at 2-6℃ / min; then increase the temperature to 1000℃ at 5-10℃ / min; and then increase the temperature to 1100~1350℃ at 2-5℃ / min and hold for 2-4 hours.
9. The method for preparing porous calcium feldspar aggregate according to claim 8, characterized in that, The process parameters for gradient segmented temperature-controlled sintering are as follows: 50-200℃ with a temperature increase of 2-6℃ / min; then 5-10℃ / min to 1000℃; then 2-6℃ / min to 1100℃ and hold for 2-3 hours; finally 2-4℃ / min to 1200-1350℃ and hold for 1-2 hours.
10. The application of the porous calcium feldspar aggregate according to any one of claims 1-5 in kilns, heat-insulating furnace linings, and refractory materials.